Active Compression-Decompression Resuscitation and Impedance Threshold Device for Out-of-Hospital Cardiac Arrest. Issue 4 (April 2015) - Wang, Chih-Hung; Tsai, Min-Shan; Chang, Wei-Tien; Huang, Chien-Hua; Ma, Matthew Huei-Ming; Chen, Wen-Jone; Fang, Cheng-Chung; Chen, Shyr-Chyr; Lee, Chien-Chang
<x xml:space="preserve">Abstract</x> Objective: Active compression-decompression resuscitation and impedance threshold device are proposed to improve survival of patients of cardiac arrest by lowering intrathoracic pressure and increasing cardiac output. The results of clinical studies of active compression-decompression resuscitation or impedance threshold device were controversial. This metaanalysis pooled results of randomized controlled trials to examine whether active compression-decompression resuscitation or impedance threshold device would improve outcomes of out-of-hospital cardiac arrest in comparison with standard cardiopulmonary resuscitation and to explore factors modifying these effects. Data Sources: Medline and Embase were searched from inception to September 2013. Study Selection: Randomized controlled trials comparing active compression-decompression resuscitation or impedance threshold device with standard cardiopulmonary resuscitation in out-of-hospital cardiac arrest patients were selected. There were no restrictions for language, population, or publication year. Data Extraction: Data on study characteristics, including patients, intervention details, and outcome measures, were independently extracted. Data Synthesis: Fifteen trials, including 16, 088 patients, were identified from 331 potentially relevant references. Return of spontaneous circulation was designated as the primary outcome. The pooled result showed no significant improvement in return of spontaneous circulation by active compression-decompression resuscitation or impedance threshold device in comparison with standard cardiopulmonary resuscitation (risk ratio, 1.04; 95% CI, 0.93–1.16; I2, 46%). There was also no significant difference in survival or neurologic outcome at hospital discharge between active compression-decompression resuscitation or impedance threshold device and standard cardiopulmonary resuscitation. The meta-regression indicated that this minimal effect might be modified by two important prognostic factors, that is, witnessed status and response time. After adjustment of these two factors, impedance threshold device appeared to improve return of spontaneous circulation, which could be further augmented by advanced airway use. Conclusions: Active compression-decompression resuscitation or impedance threshold device seemed not to improve return of spontaneous circulation in out-of-hospital cardiac arrest patients. The meta-regression indicated two probable prognostic factors causing this minimal effect. Nonetheless, these findings referred to differences between trials and could not necessarily be extrapolated to individual patients. The individual patient-level extrapolation may need to be solved by a future randomized controlled trial.